Utilization of WhatsApp Application Features and Zoom Cloud Meetings as Online Learning Media during the Covid-19 Pandemic at Madrasah Tsanawiyah An-Nashihin Kademangan - Lili Hermawati; Miftakhul Arif; Dewi Marina (Journal of Indonesian Islamic Studies, 2022)
This study aims to describe the Utilization of WhatsApp Application Features and Zoom Cloud Meetings as Online Learning Media during the Class IX Covid-19 Pandemic at MTs An-Nashihin Kademangan, inhibiting factors and supporting factors in the use of WhatsApp application features and zoom cloud meetings as online learning media. During the covid-19 pandemic class IX at MTs An-nashihin Kademangan and solutions that were carried out to overcome obstacles that occurred in the use of the WhatsApp application features and zoom cloud meetings as online learning media during the covid-19 pandemic class IX at MTs An-Nashihin Kademangan This research was conducted at MTs An-Nashihin Kademangan, South Tangerang City from February 8, 2022, to February 21, 2022. This type of research is qualitative descriptive. The study results show that teachers have utilized the WhatsApp application features and zoom cloud meetings to support online learning activities by utilizing various available features such as photo, video, document, video calls, and video conferencing. From the results of this study, it is recommended that educators further improve their competence regarding the use of ICT so that the readiness to learn using technology-based learning can be maximized.